Shear Wave Elastography in the Diagnosis of Hand Tumours - Debora Schivo; Ergys Gjika; Aurélien Traverso; Sébastien Durand (Case Reports in Orthopedics)
Diagnosis of hand tumours by conventional imaging remains difficult. Shear wave elastography (SWE) is a noninvasive method used to quantitatively assess the mechanical properties of tissues. We provide the first report of “histoelastographic” data concerning a finger tumour. Our data support the notion of ultrasound assessment using multiple parameters including morphology, elasticity, viscosity, and microflow vascularization likely contributing towards a more precise diagnosis in the future.